Analisis Pengembangan dan Keuntungan Usaha Dodol di Pasar Bengkel Kecamatan Perbaungan - Tri Novianta Yohana Sihombing; Gustami Harahap; Khairul Saleh; Fastabiqul Khairad (Universitas Medan Area, 2021)
This study aims to determine the development of dodol business and how much profit dodol producers in Village Bengkel, Perbaungan District, Serdang Bedagai Regency. This research was conducted from January 2019. This study used the sampling method by simple random sampling, in this study the sample used was 30 respondents. The sample in this study were dodol entrepreneurs living in Village Bengkel, Perbaungan District, Serdang Bedagai Regency. Based on the results of research to find out progressive strategies in the dodol business, to maintaining good quality products to increase dodol demand, maintaining affordable product prices for consumers to get regular customers and adding new customers, the relationship between business owners and dodol-making workers is runs well, the dodol-making workers are active, and the method of making it is quite easy and used manually.